Hello, let's note
[tex]f(x)=x^4-3x^3+x^2+3x-2\\\\f(1)=1-3+1+3-2=0[/tex]
So we can put (x-1) in factor. We are looking for a and b such that
[tex]f(x)=(x-1)(x^3+ax^2+bx+2)=x^4+(a-1)x^3+(b-a)x^2+(2-b)x-2[/tex]
We identify the like terms, it comes
a-1=-3 <=> a = -2
b-a=1 <=> b = 1 + a = -1
2-b=3
So it comes.
[tex]f(x)=(x-1)(x^3-2x^2-x+2)[/tex]
And we can go further using the same method to find that
[tex]x^3-2x^2-x+2=(x-1)(x^2-x-2)[/tex]
The sum of the zeroes is 1=2-1 and the product is -2=(-1)*2, so, we can factorise.
[tex]\boxed{f(x)=(x-1)^2(x+1)(x-2)}[/tex]
The sign of f(x) is the same as the sign of (x+1)(x-2) as a square is always positive.
To find the sign of a product, we can apply the following.
"- multiplied by - gives +"
"+ multiplied by + gives +"
"- multiplied by + gives -"
"+ multiplied by - gives -"
This is this what we are doing below.
[tex]\begin{array}{|c|ccccccc}x&-\infty&&-1&&2&&+\infty\\---&---&---&---&---&---&---&---\\x+1&-&-&0&+&3&+&+\\---&---&---&---&---&---&---&---\\x-2&-&-&-3&-&0&+&+\\---&---&---&---&---&---&---&---\\f(x)&+&+&0&-&0&+&+\\\end{array}[/tex]
So, to answer the question
[tex]\Large \boxed{\sf \bf \ f(x) < 0 <=> -1 < x < 2 \ }[/tex]
Thank you.